Changes in People's Habits From Conventional Shopping to Shopee E-commerce In Padangpanjang City, West Sumatra Province - Twidi Ramadhani; Yulika, Febri; Oktayanty, Yetty (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research is entitled Changes in Community Habits from Conventional Shopping to Shopee E-commerce in Padangpanjang City, West Sumatra Province. The purpose of this study is to explain the factors that cause changes in shopping activities and how the form of change that occurs due to shopee E-commerce shopping habits. The theory used in this research is the modernization theory of Talcott Parsons. Talcott Parsons defines that the development process carried out by developing countries today can be achieved when following the process carried out by developed countries, distinguishing between "modern" and "traditional" where technology plays a key role in this theory. The method used is a qualitative method with data collection techniques of observation, interviews and documentation. The results of this study discuss the factors that cause changes in conventional shopping activities to shopee e commerce shopping, namely E-commerce as a shopping forum for the community, people's consumptive behavior, and people's hedonism style. The occurrence of factors that cause changes in E-commerce shopping has an impact on forms of change such as changes in shopping activities, changes in shopping places, and changes in payment procedures.